Penyisihan Kadar Fe Dan Warna Pada Air Gambut Secara Koagulasi – Flokulasi Dengan Menggunakan Biokoagulan Kulit Pisang Kepok (Musa Acuminate) - Mutiara Nursyarah; Dewi Fitria; Syarfi Daud (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Kepok banana peel (Musa Acuminate) is easily to find in solid waste in Indonesia.. One of the uses of the solid waste of Kepok banana peel is that it can be used as a natural coagulant in water treatment. In this study, Kepok banana peels were used as a natural coagulant in the coagulation process to remove Ferric content and color of peat water. Peat water was taken from Rimbo Panjang Village, Kampar Regency. Kepok banana peels was dried using oven with 60 oC temperature for 1 hour 20 minutes. Kepok banana peels are then blended into powder and sieved using a 100 mesh sieve. The coagulant dosages used in this study was 4 gr / L; 8 gr / L; 12 gr / L; 16 gr / L; 20 gr / L; 24 gr / L; and 28 gr / L. The rapid mixing speed used was 250 rpm for 1 minute and the slow mixing speed were 90 rpm, 50 rpm, and 20 rpm for 15 minutes respectively. The results of this study showed that the concentration of Fe in peat water decreased by 0.7551 mg / L with a removal efficiency of 54.23%. Different resuts found in the color parameter, the natural coagulant of Kepok banana peel was not able to remove the color in the peat water. Keywords: Coagulation-Flocculation, Kepok Banana Peels, Natural Coagulants, Peat Water